The Effect of Product Knowledge and Market Orientation on Business Performance in MSMEs - Dewangga, Rakay Wastu; Nugroho, Sidiq Permono (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Globalization has had a significant impact on the business world, especially in terms of expanding market reach and increasing competition. In the growing digital era, information and communication technology has affected many aspects of human life, including the business sector. The development of digital technology has accelerated the pace of business and enabled access to global markets on a larger and more efficient scale. This study aims to analyze the effect of product knowledge and market orientation on firm business performance mediated by product innovation and omnichannel on MSMEs in Boyolali district. There were 100 respondents in this study through an online survey using google form with a Likert scale. The sampling technique uses non probability sampling using the slovin method. Data analysis using SmartPLS. Validity and reliability tests using smart PLS analysis on the outer model. Hypothesis testing using the SmartPLS inner model. The analysis results show that Product Innovation is able to mediate the relationship between Market Oriented and Firm Business Performance and Omnichannel is able to mediate the relationship between Market Oriented and Firm Business Performance.